Engineering materials. 1 : an introduction to properties, applications and design - Ashby, M. F.; Jones, David R. H. 1945- (Butterworth-Heinemann, 2018)
This text gives a broad introduction to the properties of materials used in engineering applications, and is intended to provide a course in engineering materials for students with no previous background in the subject.